Matrix wavefront reduction by alternating directions of node renumbering - Kurowski, Zdzisław (Computer Assisted Methods in Engineering and Science; Vol 1 No 1-2 (1994), 2023)
The paper presents a heuristic method of node renumbering for wavefront reduction of the coefficient matrix of a linear system of equilibrium equations obtained in Finite Element (FEM) or in Finite Difference (FDM) methods for regular rectangular domains. From among all the node renumbering techniques for the Banachiewicz-Cholesky triangular decomposition of an assembled matrix with a compact (the least sparse possible) profile, the method presented herein assures the best reduction of matrix wavefront and time of decomposition.